Review of current and future directions of antiviral therapy of influenza and acute respiratory viral infections in Russia - N Y Pshenichnaya; V A Bulgakova; E V Volchkova; E N Kareva; E P Selkova; V N Gorodin (Терапевтический архив, 2019)
Aim: to determine the perspectives for the use of drugs with combined antiviral, anti - inflammatory and immunomodulatory activity on the basis of medical studies of existing antiviral drugs for the treatment of influenza and acute respiratory viral infections in Russia. Materials and methods. A brief review of the antiviral drugs used in Russia for the treatment of influenza and acute respiratory viral infections was conducted on the basis of 37 articles published in Scopus, Web of Science (WoS), and RSCI databases in the period from 1997 to 2018. Results. Resistance to neuraminidase inhibitors (oseltamivir, zanamivir), is slowly developing due to the mutations of the neuraminidase gene H275Y and Q136K. Most influenza A viruses remain resistant to adamantane antivirals. Repeated use of immunomodulators with indirect antiviral action leads to a hyporeactivity of the immune system and, subsequently, to a decrease in their effectiveness. Positive clinical and laboratory data in clinical trials were obtained using Enisamium iodide, a drug with combined action - direct antiviral, and immunomodulatory. Conclusion. According to the WHO strategy, the results of the review demonstrate the need for continued research of medications with combined antiviral and pathogenetic effects on the infectious process caused by influenza and acute respiratory viral infections.